Paralytic shellfish toxins in Peruvian scallops associated with blooms of Alexandrium ostenfeldii (Paulsen) Balech & Tangen in Paracas Bay, Peru. (December 2021) - Cuellar-Martinez, Tomasa; Huanca Ochoa, Aurora del Rocío; Sánchez, Sonia; Aguirre Velarde, Arturo; Correa, David; Egoavil Gallardo, Kilder Antonio; Luján Monja, Henry Fernando; Ipanaqué Zapata, Juan Manuel; Colas, François; Tam, Jorge; Gutiérrez, Dimitri
Abstract: In recent years, dense Alexandrium ostenfeldii blooms have been reported in different coastal areas. In this study, we report for the first time the occurrence of A. ostenfeldii blooms associated with the detection of paralytic shellfish toxins (PSTs) in the Peruvian scallop ( Argopecten purpuratus ) from Paracas Bay. Alexandrium ostenfeldii blooms occurred at the end of summer and early fall, after the increase of riverine input and under stratified conditions following a decrease in wind velocity. The highest abundances occurred during warm sea surface temperatures (18–27 °C). High PST concentrations that exceed the maximum permissible level (800 μg STX eq. kg −1 ) occurred even under low A. ostenfeldii abundances (20 × 10 3 cells l −1 ). Our results contribute to a better understanding of the dynamics of A. ostenfeldii in coastal systems influenced by riverine inputs and upwelling and can be used to improve monitoring programs and allow the implementation of mitigation measures along the Peruvian coast. Highlights: Toxins in scallops and abundance of Alexandrium species abundances were studied. River input and the decrease in wind velocity favored Alexandrium ostenfeldii blooms. High toxin concentration was detected in low abundances of Alexandrium ostenfeldii . The highest abundances of Alexandrium ostenfeldii occurred under warm temperatures. Role of cyst in the development of blooms needs to be further investigated.